ANALISIS PENGARUH KOMPETENSI TERHADAP PENILAIAN KINERJA DOSEN DALAM MATA KULIAH PRAKTIKUM ANGGARAN DARI PERSPEKTIF MAHASISWA STIE MADANI BALIKPAPAN - Harianto, Rudy Pudjut (Fakultas Ekonomi Universitas Wisnuwardhana, 2016)
Abstract: This research aims to analyze the influence of competenciestoward performance assessment of lecture in the budget practicelearning from student’s perspective on STIE Madani Balikpapan.Data analyse method that used in this research are validity andreliability test; classical assumption test (normality, multicollinierity,heteroscedasticity, autocorrelation); and Multiple Linier RegressionAnalyse (correlation coeficient, determination coeficient, t test/significantion test). Accumulatively, coeficient correlation (R) = 0,656so that it can be said that the independent variables toward dependentvariable in this research can giving the strength correlation. Result ofdetermination coefficient (R2) = 0,414 it can be said the independentvariables can be explain the dependent variable of equal to 41,4%only. While the rest equal to 58,6% explained by other variable fromoutside model. The result of significantion test could be explained :(1) there are have a significant effect of Pedagogical Competenceon Lecture Performance; (2) there are have a significant effect ofProfesional Competence on Lecture Performance; (3) and thereare have a significant effect of Personality Competence on LecturePerformance; (4) there aren’t have a significant effect of SocialCompetence on Lecture Performance.Keywords : Pedagogical Competence, Profesional Competence,Personality Competence, Social Competence, , Lecture Performance.